Recess Analysis as An Aggregation of Interests - Ananda, Salsha; Munandar, Moh. Aris; Sunarto, Sunarto; Setiawan, Wahyu Benny Mukti (Universitas Negeri Semarang, 2024)
In a democratic society, one of the functions of the government is the aggregation of interests. One way to implement interest aggregation in political parties is through the conduct of recess, which is a period during which members of parliament or Regional Legislative Council (DPRD) and National Legislative Council (DPR) engage in activities outside of sessions, commonly referred to as working visits. Research results indicate how the process and flow unfold during recess activities conducted by members of the GERINDRA party faction in the Central Java province. Members of the council involved in recess activities are equipped with recess materials, which are also provided to the constituents present in the respective electoral districts ( DaPil ). During the implementation of recess activities, there is a process of absorbing aspirations, collecting aspirations, and evaluating implemented aspirations or proposals. Furthermore, obstacles arise during the recess activities, and specific strategies are employed by members of the DPRD GERINDRA party faction in the Central Java province in implementing interest aggregation.